Evidence of renal angiomyolipoma neoplastic stem cells arising from renal epithelial cells. Issue 1 (December 2017) - Gonçalves, Ana; Adlesic, Mojca; Brandt, Simone; Hejhal, Tomas; Harlander, Sabine; Sommer, Lukas; Shakhova, Olga; Wild, Peter; Frew, Ian
Abstract Renal angiomyolipomas (AML) contain an admixture of clonal tumour cells with features of several different mesenchymal lineages, implying the existence of an unidentified AML neoplastic stem cell. Biallelic inactivation ofTSC2 orTSC1 is believed to represent the driving event in these tumours. Here we show that TSC2 knockdown transforms senescence-resistant cultured mouse and human renal epithelial cells into neoplastic stem cells that serially propagate renal AML-like tumours in mice. mTOR inhibitory therapy of mouse AML allografts mimics the clinical responses of human renal AMLs. Deletion ofTsc1 in mouse renal epithelia causes differentiation in vivo into cells expressing characteristic AML markers. Human renal AML and a renal AML cell line express proximal tubule markers. We describe the first mouse models of renal AML and provide evidence that these mesenchymal tumours originate from renal proximal tubule epithelial cells, uncovering an unexpected pathological differentiation plasticity of the proximal tubule. Renal angiomyolipomas (AML) contain a mix of clonal tumour cells. Here, through reverse tumour engineering experiments, mouse genetics and analyses of human AML tumours, the authors provide evidence that these mesenchymal tumours originate from renal proximal tubule epithelial cells.